Patterns of mother-daughter communication for reproductive health knowledge transfer in Southern Nigeria (2012)
Many reproductive health studies have examined trends and outcomes of adolescent sexual behaviour but have overlooked the patterns of reproductive communication between mothers and daughters that have implications on girls’ reproductive wellbeing. Although there is a need to safeguard adolescent health, not enough work exists at the interface between female reproductive change and communication. The patterns of communication determine the effectiveness of reproductive knowledge transfer to safeguard girls’ reproductive health at a time of social change. Despite widespread opinion about the taboo nature of sexual and reproductive communication in traditional African settings, its prevalence among mothers and daughters in Ugep, Nigeria, was found to be quite high. The context, form, direction and level of communication reveal that the females engage in reproductive communication in a private environment and through peaceful and friendly strategies. Communication is achieved through sharing of meaning and mutual understanding, which has implications for adolescent female reproductive health.